2004
DOI: 10.1002/cyto.a.20079
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput laser‐mediated in situ cell purification with high purity and yield

Abstract: Background: Technologies for purification of living cells have significantly advanced basic and applied research in many settings. Nevertheless, certain challenges remain, including the robust and efficient purification (e.g., high purity, yield, and sterility) of adherent and/or fragile cells and small cell samples, efficient cell cloning, and safe purification of biohazardous cells. In addition, existing purification methods are generally open loop and exhibit an inverse relation between cell purity and yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 29 publications
0
54
0
Order By: Relevance
“…A valuable feature of the developed approach is, indeed, the possibility to perform multiple acquisitions on the same sample. The ability to relocate events based on a first analysis has been already validated in both slide-based LSC and high-resolution microscopy (1,3,14,(50)(51)(52)(53)(54)(55)(56). We demonstrated that, in our approach, a first acquisition could be exploited to target in-silico identified subpopulations.…”
mentioning
confidence: 78%
“…A valuable feature of the developed approach is, indeed, the possibility to perform multiple acquisitions on the same sample. The ability to relocate events based on a first analysis has been already validated in both slide-based LSC and high-resolution microscopy (1,3,14,(50)(51)(52)(53)(54)(55)(56). We demonstrated that, in our approach, a first acquisition could be exploited to target in-silico identified subpopulations.…”
mentioning
confidence: 78%
“…A laser can mediate photothermal, photochemical, and photomechanical effects on cells. 41 The laser-mediated effects can be used to wound the cell monolayer, as shown in Figure 1H. In this method, the cells in the predefined wound region were eliminated by laser ablation based on the photomechanical effect.…”
Section: Optical Methodsmentioning
confidence: 99%
“…At lower magnification, Cyntellect (San Diego, CA) has reported microscope image-based ablation at a rate of 100,000 cells/s with as many as 2,000 cells/s (or 2%) contaminant cells (4). Achieving 100% ablation at practical rates will also depend on other experimental variables including staining brightness, but it seems possible to achieve the appropriate rates if high enough detection specificity can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…This high-content and multiplexed image analysis based cytomics approach enables use of the cytomics data that will be crucial for unequivocal identification of heterogeneous contaminant cancer cells (3). Imaging systems can use negative sorting (via laser ablation) to kill the unwanted cells (4), and automation of an increasing array of microscope-based positive sorting techniques for transferring selected cells (e.g., LMPC, P.A.L.M. Microlaser Technologies GmbH, Bernried, Germany) offers a bright future for positive sorting.…”
mentioning
confidence: 99%